2004
DOI: 10.1002/glia.20118
|View full text |Cite
|
Sign up to set email alerts
|

Cytoprotection against oxidative stress‐induced damage of astrocytes by extracellular ATP via P2Y1 receptors

Abstract: Oxidative stress is the main cause of neuronal damage in traumatic brain injury, hypoxia/reperfusion injury, and neurodegenerative disorders. Although extracellular nucleosides, especially adenosine, are well known to protect against neuronal damage in such pathological conditions, the effects of these nucleosides or nucleotides on glial cell damage remain largely unknown. We report that ATP but not adenosine protects against the cell death of cultured astrocytes induced by hydrogen peroxide (H2O2). ATP amelio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

8
67
1

Year Published

2006
2006
2019
2019

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 66 publications
(76 citation statements)
references
References 93 publications
(110 reference statements)
8
67
1
Order By: Relevance
“…Following several studies which reported that extracellular ATP stimulation promotes intracellular ROS generation 33,[38][39][40] , we also confirmed the involvement of ATP in increasing ROS. We then investigated changes in ROS level induced by ATP decrease in the presence of antioxidants such as DMSO, NAC, and V.C.…”
Section: Trx-1 Expression In Response To Ros Via Activation Of Nadph supporting
confidence: 86%
See 1 more Smart Citation
“…Following several studies which reported that extracellular ATP stimulation promotes intracellular ROS generation 33,[38][39][40] , we also confirmed the involvement of ATP in increasing ROS. We then investigated changes in ROS level induced by ATP decrease in the presence of antioxidants such as DMSO, NAC, and V.C.…”
Section: Trx-1 Expression In Response To Ros Via Activation Of Nadph supporting
confidence: 86%
“…Several recent studies have shown that purinergic signaling via extracellular ATP stimulates DNA repair and antioxidant activity [30][31][32][33] . Our previous studies of the effect of low dose gammaand UVB-radiation on ATP release from HaCaT cells 34,35) …”
Section: What Is Purinergic Signaling?mentioning
confidence: 99%
“…Native astrocytes have been reported to express both P2Y 1 and P2Y 12 receptors [7,23]. In the present study, stably transfected astrocytoma cells that do not express these receptors endogenously were used.…”
Section: Discussionmentioning
confidence: 99%
“…Astrocytic ATP release is involved in modulating a variety of neuronal activities, affecting excitability [6], synaptic transmission [7,8], cell death [9], growth and survival [9,10]. ATP released from astrocytes also modulates the activities of astrocytes [11,12] and microglia [13][14][15] through the stimulation of purinergic receptors.…”
Section: Introductionmentioning
confidence: 99%